Impact Analysis of NPP Construction on National Economy Using Empower Model - Suparman Suparman; Nuryanti Nuryanti; Elok Satiti Amitayani (Jurnal Pengembangan Energi Nuklir, 2020)
The Nuclear Power Plant (NPP) could be one of the generation technology options to fulfill the mandate of Government Regulation No. 79 of 2014 which targeted the New Renewable Energy (NRE) portion in the national energy mix amounted to 23% by 2025 and 31% by 2050, while the realization of NRE until year 2019 is 12,6%. Any implementation of a new project or industry will have an impact on both national and region economy, and NPP project is no exception. This study aims to analyze the impact of nuclear power plant development on the national economy sector. The economic parameters analyzed in this study focused on gross domestic product (GDP) and employment. The analysis was done by using Input Output model with EMPOWER(An Extended Input-Output Model for Impact Assessment of Nuclear Power Plants) model released by IAEA as a tool. Construction period for 2 units of NPP 1000 MWe is assumed 10 years including site preparation. The results of the analysis showed that NPP construction has a significant impact on GDP and employment absorption. Each of module (A, AB, ABC and ABCD) had an impact of GDP increase of 0.021%, 0.033%, 0.040% and 0.040% respectively when compared to the GDP gained without any NPP construction. As for the amount of employment creation in module A, AB, ABC and ABCD respectively equal to 66,083, 107,693,86,081 and 85,449.It is can be concluded that according to the analysis provided by the EMPOWER, the construction of a NPP has positive impacts on the national economy.